A paradigm shift in audiology education. - Sweetow RW; Davis A; Hickson L (Audiology Today)
The mode of education for health-care professionals is currently experiencing a paradigm shift. Rather than strict didactic teaching, consisting primarily of lectures and grand rounds, healthcare professionals are now more aware of the relevance of problem-based learning. There is a need for problem-based educational opportunities so that audiologists can adopt client-centered approaches.